First experiences with the global minimum tax and the difficulties of determining tax residency: key takeaways from the IFA’s 77th Congress in Lisbon in 2025 - Erdős, Gabriella; Fábics, István (Public Finance Quarterly, 2025)
The International Fiscal Association (IFA) was founded in the Netherlands in 1938 with the aim of promoting the development of international and comparative tax law and public finance. The organization is unique in that its members include an equal proportion of experts from the public and private sectors, including tax authority leaders, ministry decision-makers, scientists, lawyers, consultants, and corporate tax directors. Headquartered in Rotterdam, it currently has more than 70 national branches and approximately 14,000 members. The IFA’s annual World Congress is the most important forum for international taxation, where theoretical research and practical experience converge. The 77th Congress, held in Lisbon in 2025, was particularly significant because 2024 marked the first year of implementation of the global minimum tax (Pillar II) in the European Union. Key topics included redefining corporate residency in the digital age and combating the misuse of double taxation agreements. Representatives from the OECD, the European Commission, the IMF, the World Bank Group, IOTA, CIAT, and ICC, and the presentations and seminars provided a comprehensive overview of the rapidly changing international taxation system, the balance between legal certainty and competitiveness, and the directions for developing a modern, transparent, and coherent tax policy.